E-COMMERCE TUMBAS DAGING - Bethananda, Caesarico Ariaundhi; Cholil, Saifur Rohman (Universitas Semarang, 2021)
The name Tumbas Daging comes from the word Tumbas which in Javanese means Buy and use the word Meat because this system sells meat products. Tumbas Daging in collaboration with fresh meat seller Sumber Rezeki, Sumber Rezeki is one of the businesses engaged in the beef trade, Sumber Rezeki itself is located at Jalan Banteng Raya No.4, Semarang City. Sumber Rezeki has a few problems with sales during Eid because the demand for meat is increasing, therefore with the E-Commerce tumbasdaging.com, selling meat at Sumber Rezeki is made easier because buyers or customers do not have to come to the shop to buy meat, but buyers or customers can buy meat at Sumber Rezeki through E-Commerce tumbasdaging.com. Tumbas Daging using the prototyping method in this study aims to get an overview of the applications that will be built through the development stage of the Prototype application first which will be evaluated by the Sumber Rezeki meat seller. The Prototype application that has been evaluated by Sumber Rezeki will be used as a reference in making applications that will be used as E-Commerce for Tumbas Daging. The purpose of this collaboration with Sumber Rezeki is to be able to build Tumbas Daging E-Commerce so that it can be used by many people to sell beef or purchase beef through the website tumbasdaging.com.